A Resource-Based Theory of Market Structure and Organizational Form - Van Witteloostuijn, Arjen; Boone, Christophe (Academy of Management Review, 2006)
We argue that combining the insights from both the industrial organization and organizational ecology perspectives is likely to produce value added. We develop are source-based theory of market structure, where resources pertain to the environmental assets (together forming the resource space) without which a firm cannot operate viably. We propose that the distributive shape of the resource space, together with the presence or absence of exploitation economies, molds market structures in terms of density and concentration. Our theory unifies many unconnected strands of theory in the organization sciences domain.